1981
DOI: 10.1007/bf00251278
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment of Type 2 (insulin independent) diabetes mellitus on plasma concentrations of pancreatic polypeptide and glucagon

Abstract: Summary. The effect of the control of diabetes with diet and insulin upon plasma levels of human pancreatic polypeptide and glucagon was determined in eight patients with Type 2 (insulin independent) diabetes mellitus. The mean + SEM fasting plasma glucose was 15.9 _+ 1.3 mmol/1 for 5 days of diet treatment and 5.9 _+ 0.4 mmol/l for the last 5 days of treatment with diet plus insulin (p < 0.0001); corresponding fasting plasma pancreatic polypeptide levels were 328 _+ 97 and 247 + 71 pg/ml (p < 0.05) and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…This is in accordance with the finding that normalisation of fasting plasma glucose by short-term treatment with diet plus insulin is associated with decreases in basal and stimulated secretory activity of the pancreatic polypeptide cells in type 2 diabetes (Berger et al, 1981). Thus, the decrease of PP in our study may be caused by a decrease in fasting plasma glucose.…”
Section: Discussionsupporting
confidence: 94%
“…This is in accordance with the finding that normalisation of fasting plasma glucose by short-term treatment with diet plus insulin is associated with decreases in basal and stimulated secretory activity of the pancreatic polypeptide cells in type 2 diabetes (Berger et al, 1981). Thus, the decrease of PP in our study may be caused by a decrease in fasting plasma glucose.…”
Section: Discussionsupporting
confidence: 94%
“…Amino acids themselves stimulate protein synthesis and high glucagon attenuates this effect (38). The present data are in agreement with previous findings that showed that normalization of hyperglycemia in people with type 2 diabetes with prolonged insulin treatment is associated with decreases in basal glucagon concentrations and in oral protein stimulated glucagon response (35). A smaller glucagon response in insulin‐treated subjects also suggests that the glucagon sensitivity to protein was improved.…”
Section: Discussionsupporting
confidence: 94%
“…Inappropriate hyperglucagonemia in response to glucose and protein is recognized as a common feature that unfavorably influences diabetes control (34). Glucagon is normally suppressed by hyperglycemia (35). The lack of glucagon suppression by hyperglycemia in diabetes has been explained by a relative deficiency of glucose within the alpha cells, secondary to insulin deficiency, which is restored by insulin infusion (36), a potent inhibitor of glucagon secretion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plasma pancreatic poly¬ peptide (PP) levels in diabetic subjects increases not only at the fasting state (Bergen et al 1981;Floyd et al 1977;Mizuno et al 1979), but also during the diabetic ketoacidosis (Skare et al 1980) or after ingestion of beef or a test meal (Bergen et al 1981;Floyd et al 1977;Ishida et al 1981). Morphologicallv the PP cells in the islets of the juvenile diabetic pancreas show hyperfunctioning activity (Gepts et al 1977).…”
mentioning
confidence: 97%